Scientology a new slant on life - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Los Angeles, California Bridge Publications, Inc., 2007)
What are your goals? Where are you going? Why are you here? What are you? Scientology has answers to these questions, good answers that are true, answers that work for you. For the subject matter of Scientology is you.
Sound discs contents: Introduction -- Is it possible to be happy? -- Scientology : an overview. Personal integrity ; A description of scientology ; How to study scientology ; Man's search for his soul -- On the mind and survival. On our efforts for immortality ; On raising our level of consciousness -- On the fundamentals of life and living. The eight dynamics ; The affinity, reality and communication triangle ; The reason why -- On work and success. Handling the confusions of the workaday world ; The man who succeeds ; A true group -- On family. On marriage ; How to live with children -- On how to get along with others. Two rules for happy living ; What is greatness? -- On human behavior. The anti-social personality ; The social personality ; The third party law -- On honesty and ethics. Honest people have rights, too ; Ethics, justice and the dynamics -- In closing : the true story of scientology -- Epilogue : my philosophy.
"A Hubbard publication".
Includes bibliographical references and index.
Keywords: Scientology